Ecology of Scots pine (Pinus sylvestris L.) in Ireland - preliminary results - MITCHELL, FRASER JOHN GRAY; ROCHE, JENNIFER; WALDREN, STEPHEN (Environmental Sciences Association of Ireland, 2008)
The ecology of Pinus sylvestris in Ireland has not been adequately described. Research to determine its native status in Ireland has produced ambiguous results. P. sylvestris is being widely planted in semi-natural habitats. However, neither the ecological value of these plantations nor the optimum environmental conditions for P. sylvestris planting in Ireland have been determined. This study aims to provide reliable, consolidated information on the autecology and biodiversity value of P. sylvestris in Ireland. Data on vegetation, soil characteristics, stand structure and regeneration have been recorded at ten sites throughout the country to date. P. sylvestris occupies a wide variety of habitats in Ireland. Preliminary data analysis has shown that there is a low level of species constancy within P. sylvestris communities and therefore the communities are variable. Three distinct vegetation types are apparent and soil pH and altitude are important factors in determining their floristic composition.
PUBLISHED
Keywords: woodland ecology; plant community ecology; Pinus sylvestris L.; Ireland; reintroduction